Spent pleurotus ostreatus substrate has potential for managing Fusarium Wilt of Banana - Ocimati, Walter; Were, Evans M.; Tazuba, Anthony Fredrick Kadama; Dita Rodriguez, Miguel Angel; Zheng, Si-Jun; Blomme, Guy (MDPI, 2021)
A range of basidiomycetes including the edible mushroom Pleurotus ostreatus (Po) can suppress plant pathogens such as Fusarium spp. With the current increase in production and consumption of Po in Uganda, the spent Po substrate (SPoS) could be an alternative to manage Fusarium wilt of banana (FWB), caused by the soil borne pathogen Fusarium oxysporum f. sp. cubense, race 1 (Foc). This study determined the potential of SPoS to inhibit Foc in vitro and in potted plants. In vitro studies conﬁrmed suppression of Foc in pure co-culture (Po vs. Foc) assays and media amended with different concentrations (0% to 50% w/v) of un-sterilized SPoS ﬁltrates. Foc growth in the sterile SPoS ﬁltrate was comparable to the water control, suggesting possible roles of biotic or thermolabile components of the SPoS. To further verify the suppressive effects of SPoS, pot experiments were carried out with a resistant (‘Mbwazirume’, AAA) and susceptible (‘Sukali Ndizi’, AAB) banana cultivar using both artiﬁcially and naturally infested soils. Independent of the inoculation method, SPoS signiﬁcantly reduced the severity of FWB in pot experiments. Susceptible cultivar ‘Sukali Ndizi’ growing in substrates amended with SPoS showed lower (1.25) corm damage (Scale 0–5) than the un-amended control (3.75). No corm damage was observed in uninoculated controls. The resistant cultivar ‘Mbwazirume’, showed slight (0.25) corm damage only in the Foc-inoculated plants without SPoS. These ﬁndings suggest that SPoS could be used as part of the management practices to reduce the impact of FWB.